Resolução de problemas ricos em contexto : análise de um grupo colaborativo - Lima, Grayce Kelly Alves Santos (2016)
The interaction within the classroom is one of the key variables in the process of teaching and learning, but these interactions between students and teachers usually do not occur in the methodologies adopted by most physics teachers. In addition, physical education and their evaluation are anchored to mathematical techniques without any connection to the everyday student. Thus, the student only memorizes the "formulas", without seeking relationships with concepts already learned by them, causing learning meaningless. Thus, we believe that social interaction linked to the collaborative activity can give meaning to the process of teaching and learning, as students build their knowledge by interacting collectively. In this way, the main objective of this research is to know the perceptions of students about the Rich Issues in Context, which is a type of collaborative teaching methodology in higher education, as well as their behavior while collaborative group in a discipline of Physics B in Federal University of Sergipe. In total, 15 students participated, the data were collected through non-participant observation and semi-structured group interview, conducted in two groups, and a survey applied to all students in the discipline. The results regarding the roles of each member of the group revealed that at times the students failed to perform their roles effectively, but then we noticed that they cooperated in the development of activities. In addition, students reported that in collaborative learning they learn from their classmates and with respect to Rich Problems in Contexts, we found that students understand the benefits of this activity and do not see this task as a way to decrease the amount of activity of each student.